Estilos de liderazgo de directores de instituciones educativas según percepción de docentes de la Red N° 2 - Distrito de Ventanilla - Callao - Juárez Campos, Roberto Carlos (2010)
The descriptive research conducted in teachers of educational institutions Francisco Bolognesi", "Villa Los Reyes", "Pedro Planas Silva" and "Fe and Joy" from the RED No. 2 District Ventanilla Callao region. A questionnaire was adapted for determine the perception of teachers regarding leadership styles of their managers, it has been validated by experts and has 0.956 reliability with Cronbach's alpha. The sample was 102 teachers chosen so stratified probability. The results show the prevalence of authoritarian leadership style in managers in these educational institutions, followed style and style liberal democracy. This mostly means that the author assumes the in a vertical direction, decisions are made individually, there are orders to be fulfilled and not takes into account the views and ideas of staff full.